2012
DOI: 10.1080/10438599.2010.536378
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive patenting: securing market exclusion and freedom of operation

Abstract: JT03275947 STI Working Paper SeriesThe Working Paper series of the OECD Directorate for Science, Technology and Industry is designed to make available to a wider readership selected studies prepared by staff in the Directorate or by outside consultants working on OECD projects. The papers included in the series cover a broad range of issues, of both a technical and policy-analytical nature, in the areas of work of the DSTI. The Working Papers are generally available only in their original language -English or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 30 publications
2
41
0
3
Order By: Relevance
“…Previous research has shown that patents citing prior art classified as an XY-type have a lower probability of being granted, are more often withdrawn by the applicant before the EPO has made a decision (Guellec et al, 2012), and have a higher probability of facing opposition after granting (Harhoff and Reitzig, 2004). The literature, therefore, concludes that XY-cited patents exhibit higher preemptive power than other patents.…”
Section: Independent Variables Preemptive Powermentioning
confidence: 75%
“…Previous research has shown that patents citing prior art classified as an XY-type have a lower probability of being granted, are more often withdrawn by the applicant before the EPO has made a decision (Guellec et al, 2012), and have a higher probability of facing opposition after granting (Harhoff and Reitzig, 2004). The literature, therefore, concludes that XY-cited patents exhibit higher preemptive power than other patents.…”
Section: Independent Variables Preemptive Powermentioning
confidence: 75%
“…These references are made to limit the scope of patent applications by evaluating their novelty with regard to prior inventions. As expected, the estimated coefficient clearly indicates that these references that patent examiner includes to delineate the patent claims make a positive grant decision less likely (Guellec et al, 2009 One could hypothesize that the patent portfolios of the largest patent applicants are better known to the patent examiners since they have to evaluate many patents from these submitters. This might impact the examination procedure of these applicants' patents.…”
Section: Ref/ref)mentioning
confidence: 85%
“…In addition to the context in which ad evice is used, it is important also to consider the intellectual property landscape of aPOC diagnostic at an early stage.Inaddition to searching the literature,r esearch to develop practical technologies should include an evaluation of the "freedom to operate"the freedom to develop and commercialize an idea without infringing upon the intellectual property of others.W hen working on technologies for LMICs,t he freedom to operate may be less well-defined than in the US or Europe.N evertheless,f or both the technologies discussed, we applied for patents 1) to make it easier to attract commercial partners for development of products for noncompetitive developed markets, [21] 2) as adefensive strategy to preserve our freedom to operate, [22,23] and 3) to provide at ool to use in crosslicensing to ease our access to intellectual property belonging to others. [22] Since intellectual property is expensive to obtain and maintain, and since one good outcome of the type of technology we wish to develop would be to have it copied and developed by others in the LMICs,t he best strategies for intellectual property are not always well defined.…”
Section: Patient Diagnosticsmentioning
confidence: 99%